Relationships between lower limb muscle volume, muscle strength and sprint performance in elite athletes - Giroux, C.; Macchi, R.; Piecuch, L.; Hegyi, A.; Hollville, E.; Mateus, D.; Fornasier- Santos, C.; Slawinski, J.; Morin, J. B.; Lacourpaille, L.; Couturier, A.; Nordez, A.; et al. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: High-speed running is fundamental to perform in various sports. Muscle morphological (volume) and functional characteristics (strength) are recognized to be associated with sprint performance [1,2] and seem to influence sprint force-power-velocity (FPV) relationship [3]. This study aimed to identify the relationships between sprint maximal velocity (Vmax), theoretical maximal power (Pmax) and force (F0) derived from the sprint FVP profiles, and lower limb muscle characteristics including volume inferred from automatized MRI scans segmentation in elite athletes. METHODS: Seventy-two athletes (33 women, 39 men, age: 24.3 ± 3.3 years, height: 1.77 ± 0.09 m, mass: 74.2 ± 12.9 kg) of rugby 7, track and field, and bobsleigh performed two 40-m sprints. Vmax and FVP relationship were assessed using radar-based velocity measurements. F0 and Pmax were calculated from the FPV relationship. Maximal isometric (MVC) and eccentric (ECC) torque, and rate of torque development (RTD) were assessed during hip, knee and ankle extension and flexion (except for ankle). The volume of 18 lower limb muscles including gluteus, quadriceps, hamstrings and adductors groups was automatically extracted from Magnetic Resonance imaging (MRI) using Deep Learning method [4] for 24 athletes (14 women and 10 men). Multiple linear regressions (Forward method) were conducted to identify significant predictors of Pmax, F0 and Vmax (dependant variables) from the functional characteristics and then the 18 muscle volumes (independent variables). RESULTS: Vmax exhibited significant correlations with the volume of the vastus intermedius (VI), gluteus minimus (Gmin), biceps femoris short head (BFsh) and semitendinosus (ST) muscles (r2 = 0.62, P < 0.05). Pmax showed significant correlations with VI, BFsh, gluteus maximus (Gmax) and ST volumes (r2 = 0.70, P < 0.05) whereas F0 showed significant correlations with VI and Gmax volume (r2 = 0.58, P < 0.05). Furthermore, Vmax was significantly correlated with plantar flexor RTD and hip flexor MVC (r2 = 0.20, P < 0.05) whereas Pmax and F0 were both significantly correlated with plantar flexor RTD and knee flexor MVC (r2 = 0.18 and r2 = 0.13, respectively, P < 0.05). CONCLUSION: This study shows that a significant part of sprint performance variability could be explained by hip flexors and knee extensors muscle volume. Joint strength testing seems also to partly explain sprint performance. Hip extensor and knee flexor muscles could be targeted in training programs to maximize sprint performance. While these findings are consistent with previous studies [1,5,6], they suggest to further explore the relationship between muscle morphology, functional capacity and sprint performance, particularly for thigh muscles.